2014
DOI: 10.1128/jcm.01397-14
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Molecular Characteristics of Carbapenem-Resistant Enterobacteriaceae in a Health Care System in Los Angeles, California, from 2011 to 2013

Abstract: c Carbapenem-resistant Enterobacteriaceae (CRE) are a concern for health care in the United States but remain relatively uncommon in California. We describe the phenotype, clonality, and carbapenemase-encoding genes present in CRE isolated from patients at a Californian tertiary health care system. CRE for this study were identified by evaluating the antibiograms of Enterobacteriaceae isolated in the UCLA Health System from 2011 to 2013 for isolates that were not susceptible to meropenem and/or imipenem. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 51 publications
4
65
4
Order By: Relevance
“…Three of these harbored the bla KPC gene, 1 harbored the bla SME gene, and 6 were PCR negative for the six carbapenemase genes tested (Table 1). These isolates were also negative for phenotypic carbapenemase production by the CarbaNP test, which was performed in another study (7). Using the Vitek 2 breakpoints, 3 MEs and 9 mEs were found ( Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of these harbored the bla KPC gene, 1 harbored the bla SME gene, and 6 were PCR negative for the six carbapenemase genes tested (Table 1). These isolates were also negative for phenotypic carbapenemase production by the CarbaNP test, which was performed in another study (7). Using the Vitek 2 breakpoints, 3 MEs and 9 mEs were found ( Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…The isolates were selected to represent a variety of resistance phenotypes that cover a wide range of MICs potentially encountered in the laboratory. Twenty-five carbapenem-resistant Enterobacteriaceae (CRE) that were previously assayed for the carbapenemase genes bla KPC , bla NDM-1 , bla VIM , bla SME , bla IMP , and bla OXA-48 were included (7). For the purpose of this study, CRE were defined as isolates with a meropenem MIC of Ͼ1 g/ml by BMD.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the Xpert Carba-R does not query for bla SME , a carbapenemase gene found sporadically on the chromosome of isolates of Serratia marcescens, including in our own patient isolates (19). While considered less of an epidemiological concern because the gene is not harbored on a plasmid, outbreaks of isolates that harbor this gene have been documented (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Some have concerns that this definition may overestimate CP-CRE because isolates resistant to ertapenem but not imipenem, meropenem, or doripenem often result from the presence of extended-spectrum beta-lactamases (ESBLs) or AmpC enzymes, which have some hydrolyzing activity against ertapenem, usually in combination with permeability defects. Similarly, some isolates without carbapenemases are resistant to imipenem, meropenem, and/or doripenem due to changes in porin proteins, often in conjunction with low-level AmpC or ESBL activities, albeit such isolates are less common (19). For instance, one study using the CDC definition found that 55% of isolates labeled as CP-CRE did not harbor carbapenemase genes (18).…”
mentioning
confidence: 99%
“…[3] Immunocompromised or debilitated patients are highly susceptible to hospital-acquired infections -either after colonisation with environmental strains or following invasive procedures, such as catheterisation, bronchoscopy, colposcopy or surgical biopsies. [4] P. rettgeri is commonly found to cause traveller's diarrhoea and has also been isolated from more severe human infections such as meningitis. [3,5,6] Among the Providencia species, P. stuartii and P. rettgeri are the most common causes of infections, especially UTIs in hospitalised patients, although other infections can occur.…”
Section: In Practicementioning
confidence: 99%